Differences in water release for the binding of EcoRI to specific and nonspecific DNA sequences. - Sidorova, N Y (1996)
The free energy difference between complexes of the restriction nuclease EcoRI with nonspecific DNA and with the enzyme's recognition sequence is linearly dependent on the water chemical potential of the solution, set using several very different solutes, ranging from glycine and glycerol to triethylene glycol and sucrose. This osmotic dependence indicates that the nonspecific complex sequesters some 110 waters more than the specific complex with the recognition sequence. The insensitivity of the difference in number of waters released to the solute identity further indicates that this water is sequestered in a space that is sterically inaccessible to solutes, most likely at the protein-DNA interface of the nonspecific complex. Calculations based on the structure of the specific complex suggest that the apposing DNA and protein surfaces in the nonspecific complex retain approximately a full hydration layer of water.